Antigens Of Pasteurella multocida Isolates From Rabbit And Their Immunologencity - Manoharan S (Department of Microbiology, College of Veterinary and Animal Sciences, 1994)
Two rabbit strains viz. R9 S and R23 S and a bovine vaccine strain P – 52 which were maintained in virulent form, were used for the preparation of three forms of antigen viz., heat inactivated crude extract, KSCN extract and sonicated antigen. These antigens were chemically analysed for protein and carbohydrate contents and were found to be higher in the sonicated antigen preparation irrespective of the source. In SDS – PAGE analysis, the profiles discerned by heat inactivated crude extract, KSCN extract and sonicated antigens were four, five and six protein bands with molecular weights lesser than 68 kDa while the KSCN extract and sonicated antigen presented an additional protein band with molecular weight higher than 68 kDa. Three types of antigen of P. multocida were characterized and analysed for the inter relationship and the immunogenic potential in mice. Antiserum was raised against each antigenic preparation from the three strains in rabbits and used for serological study. In AGPT and immunoelectrophoresis the serum developed multiple precipitin lines and arcs respectively when reacted against the three homologous and two heterologous antigens in which a few were identical to the heterologous antigens. The results revealed stronger serological relationship between the two rabbit strains than with the cattle strain and the heterogeneity of the sonicated antigen. The antibody titre in each antiserum was measured by IHA using the sensitized GA – SRBC/T – GA – SRBC and the titres were more in the homologous antiserum and high titre for the heterologous serum was seen with the sonicated antigen. The LD50 determined for the three strains R9 S, R23 S and P- 52 was found to be 3 x 104 , 3 x 103 and 3 x 105 bacteria. Immunogenic potential of the three antigens and an adjuvanted sonicated antigen were tested in mice by giving two doses of vaccine at 14 days interval and challenging on 21st day with homologous and heterologous strains. A higher percentage of protection was conferred by homologous strains and it was cent per cent (100%) with sonicated antigen. The percentage of protection against challenge with heterologous strains was low. An elaborated study on immunity trials with these immunogens is needed before recommending the R23 S as a candidate vaccine strain.